Extensive sequence divergence between the reference genomes of two elite indica rice varieties Zhenshan 97 and Minghui 63 - Zhang, Jianwei; Chen, Ling-Ling; Xing, Feng; Kudrna, David A.; Yao, Wen; Copetti, Dario; Mu, Ting; Li, Weiming; Song, Jia-Ming; Xie, Weibo; Lee, Seunghee; Talag, Jayson; et al. (National Academy of Sciences, 2016)
Indica rice accounts for >70% of total rice production worldwide, is genetically highly diverse, and can be divided into two major varietal groups independently bred and widely cultivated in China and Southeast Asia. Here, we generated high-quality genome sequences for two elite rice varieties, Zhenshan 97 and Minghui 63, representing the two groups of indica rice and the parents of a leading rice hybrid. Comparative analyses uncovered extensive structural differences between the two genomes and complementarity in their hybrid transcriptome. These findings have general implications for understanding intraspecific variations of organisms with complex genomes. The availability of the two genomes will serve as a foundation for future genome-based explorations in rice toward both basic and applied goals.